A study of employees job satisfaction in Kota Tinggi District Council / Sarina Lemat@Limat - Lemat@Limat, Sarina (2012)
Job satisfaction is one of the evaluation aspects in work behavior, which has been emphasized by all the organizations to ensure the successful of organization’s goal. This research is focus on the job satisfaction among employees in Kota Tinggi District Council. Moreover, this study will examine and measure level of satisfaction among workers in the existing services, facilities that provided to them and the management to identify the factors that influence job satisfaction among staffs. The findings showed that most of the employees have high level of satisfaction with the salary, nature of work, relationship with colleagues and also the working environment. The researcher is also able to give some recommendations and suggestion on how to improve and increase job satisfactions of the employees after the analysis, findings and interpretation. In this study, we used questionnaire techniques and other secondary data such as reports, database and so on for data collection. Data collected have been process and analyze by using Statistical Package for Social Science (SPSS) version 16.0 to produce a relevant and accurate result.